Perancangan Dashboard Vaksinasi dengan Kombinasi Design Sprint, Persona, Crazy 8’S, DAN MVP - Anwar, David Saiful; Kusuma, Wahyu Teja; Haris, M. Syauqi (STIKOM Tunas Bangsa Pematangsiantar, 2024)
In carrying out the vaccination work program, the government is required to be able to take fast and appropriate policies while maintaining efficient use of funds in each work unit. One of the government work units that also focuses on vaccination is Kodam V/Brawijaya. The factors causing vaccination data to be uninformative in Kodam V/Brawijaya's ranks are that there are many 38 Kodam V/Brawijaya work units, Kodam V/Brawijaya does not yet have an integrated vaccination information system, the time and place for carrying out vaccination activities is short and moving. moving on, the presentation of data obtained from work units is still raw and uninformative data. Based on these problems, this research aims to design a vaccination dashboard application that suits the needs of users within the TNI Kodam V/Brawijaya area. The design of the vaccination application in this research used the design sprint method. The design sprint method was chosen because based on previous research it can be relied on to produce designs quickly and in accordance with user needs. In the stages of the design sprint method in this research, it will be combined with the persona, crazy 8's, and minimum viable product (MVP) methods. This research contributes to producing a new combination of methods to solve research problems in the field of application design. Finally, the combination of the design sprint method with persona, crazy 8's, and minimum viable product (MVP) is expected to produce a vaccination dashboard application design that meets the needs of Kodam V/Brawijaya.